VARUN (CRATAEVA NURVALA BUCH-HAM): A CRITICAL REVIEW W.S.R. TO URINARY TRACT DISORDER - Nigamanand, *Bal; Suresh, Chaubey; Ramesh Chandra, Tiwari; Gagan Deep, Kour; Srishti, Dhyani (International Journal of Ayurveda and Pharma Research, 2016)
Human passion on herbal medicine dated back to times immemorial. Man is the clever living being that knows how to adapt to the changing environment of time and space. As we are all aware, the very survival of animal kingdom is depending on the plant kingdom. The plants or herbs played major part in the pharmaco therapy during the Vedic period in India. Vedic literatures indicate mainly about the utility of single herbs in management of common disease. Among all the single herbs one of the most valuable medicinal herb Varun (Crataeva nurvala Buch-Ham), which is used to treat the different disease and also maintain the healthy condition of the body system. It is a small tree having much branches belonging to family Capparidaceae. Each part of Varun tree including bark, root, leaf having certain medicinal properties. Chiefly, the bark of Varun mainly used in the treatment of urolithiasis (Asmari bhedan), the decoction of root bark mainly used in lymph adenitis (Gandamala nasan) and immature wound healing (Apakwa vidradhi) respectively. The leaf is mainly used to reduce the fattiness of the body (Medohar). Hence this paper work is prepared for the re-evolution of the therapeutic importance of the herbal plant Varun (Crataeva nurvala Buch-Ham).